Rehabilitation outcomes following tail-fluke amputation in an Indo-Pacific bottlenose dolphin: A welfare-centered approach - Suguru Higa; Sayaka Takahashi; Eri Nakashima; Yui Kurosu; Haruka Ikeshima; Ryota Yagi; Nihiro Adachi; Keiichi Ueda; Hirobumi Umeyama; Hitoshi Yamamoto; Yukinori Nakakita; Kazuma Tochigi; et al. (PLoS ONE, 2026)
Tail fluke loss in cetaceans compromises locomotion and impairs social functioning, posing serious welfare challenges. Rehabilitation strategies that address both physical performance and behavioral reintegration are essential for improving quality of life in affected individuals. This study evaluated the outcomes of a structured, two-phase rehabilitation program applied to Sami, an adult Indo-Pacific bottlenose dolphin ( Tursiops aduncus ) that underwent tail-fluke amputation, with an emphasis on locomotor function, behavioral adaptation, and long-term welfare. The rehabilitation protocol comprised two phases. Phase 1 focused on restoring vertical tail-beat locomotion through a combination of range-of-motion exercises and the use of a custom-designed prosthetic tail fluke. Swimming performance was quantitatively assessed using biologging devices under three conditions: without tail flukes, with the prosthetic tail, and in healthy conspecifics. Phase 2 introduced structured cohabitation with familiar individuals to promote social reintegration. Behavioral data were collected before and after rehabilitation to evaluate affiliative engagement and activity patterns. While maximum swim speed remained lower than in healthy individuals, propulsion per stroke significantly improved with prosthetic use. Notably, the subject dolphin retained species-typical vertical tail-beat motion even after prosthesis discontinuation, indicating motor pattern adaptation. Post-rehabilitation, affiliative behavior increased to 17% of total observed activity—more than twice that of a healthy control—while resting behavior markedly declined. No aggression or abnormal behaviors were observed. This study demonstrates that a welfare-centered, multi-phase rehabilitation framework can effectively promote both functional recovery and social reengagement in dolphins with severe caudal injuries. The long-term retention of adaptive locomotor and social behaviors highlights the potential of integrative approaches to enhance the quality of life in physically compromised cetaceans.